ANALISIS KELAYAKAN USAHA TANI UBI KAYU (Manihot esculenta) DENGAN SISTEM KEMITRAAN DI KECAMATAN LIMBANGAN KABUPATEN KENDAL - Istanto Istanto; Shofia Nur Awami; Hendri Wibowo (Universitas Wahid Hasyim, 2022)
Cassava is one of the agricultural commodities that have many uses for the community. The purpose of this study was to determine the partnership pattern of cassava farmin in Limbangan District, to determine the level of costs, revenues and income from cassava farming, BEP and the feasibility of the business seen from the R/C. The basic method of this research is analytical descriptive. Sampling of farmer respondents using the census method while supplier respondents using the purposive method. The number of respondents who were interviewed were 39 farmers and 1 supplier. As for collecting data and information with interview techniques, recording and observation. The results showed that the cassava farming partnership pattern in Limbangan District is a vendor pattern which is a partnership with the category having a direct relationship with the business sector between actors. The total cost incurred in partnership system cassava farming per production period is Rp. 6,897,598 with a cultivated land area of 3,375 m2. The total revenue is Rp. 11,971,292 per growing season. Meanwhile, the income from the partnership system of cassava farming is Rp. 5,073,694. R/C value of 1.73. This shows that cassava farming with a partnership system is feasible. The unit BEP value is 4,311 Kg and the BEP price is Rp. 922.